Commentary on the Psalms - Salah, Daniel (Bar Ebroyo Kloster Publications, 2011)
Daniel of Salah's Commentary on the Psalms was one of the foundational exegetical and theological works of the developing Syriac miaphysite tradition. The present volume presents the Syriac text of Daniel's commentary in vocalized Serto script